Метафорична модель концептів CHARM і ЧАРІВНІСТЬ в англійській і українській лінгвокультурах - Томчаковська, Юлія Олегівна; Томчаковська, Ю. О.; Томчаковская, Юлия Олеговна; Tomchakovska, Yuliia О. (My University, 2016)
У статті схарактеризовано поняттєві та образні складові концептів CHARM і ЧАРІВНІСТЬ як етноспецифічних естетичних ментальних утворень, описано семантичні умови прототипового сценарію концепту ЧАРІВНІСТЬ як кросскультурної моделі, визначено універсальні й етноспецифічні риси метафоричної моделі концептів CHARM і ЧАРІВНІСТЬ у двох лингвокультурах.

The article deals with the notional and figurative components of the concepts CHARM and ЧАРІВНІСТЬ as ethno-specific aesthetic mental formations, describes semantic conditions of the prototypical scenario of the concept CHARM as a cross-cultural model, determines the universal and ethno-specific features of the metaphorical model of the concepts of CHARM and ЧАРІВНІСТЬ in both linguistic cultures. The study results indicate that representatives of both cultures associate the common features of the esthetic concepts of CHARM and ЧАРІВНІСТЬ with both the inner and outer abilities of a person to attract, charm, and enrapture other people. The differences in the perception of these concepts are expressed in that for English speakers charm is expressed as a set of outward means for creating a pleasant communicative environment (niceness, smile, friendly attitude, humor), which is peculiar to both public figures (entertainers, actors, celebrities, etc.) and ordinary people in every-day and professional interaction. For Ukrainian speakers, ЧАРІВНІСТЬ is an inherent property related to a definite set of ethical values (faith, goodness, sincerity, integrity, forgiveness, benevolence).
Томчаковська Ю. О. Метафорична модель концептів CHARM і ЧАРІВНІСТЬ в англійській і українській лінгвокультурах / Ю. О. Томчаковська // Записки з романо-германської філології. – Вип. 1 (36) – 2016. – С. 175-180.
Keywords: естетичний; концепт; ОБАЯНИЕ; CHARM; ЧАРІВНІСТЬ; лінгвокультура; aesthetic; concept; linguistic culture